Dr. Rune Pettersson - Padovani, Stephania (InfoDesign, 2006)
Mälardalen University, Suécia Rune Pettersson, Ph.D., is Professor of Information Design at the Department of Innovation, Design and Product Development at Mälardalen University, Eskilstuna, Sweden. He is also Chairman Art & Design, Faculty of Science & Technology. Dr Pettersson has been Vice President of International Institute for Information Design, IIID. He has also been Vice President of the International Visual Literacy Association, IVLA, six times and President during 2000-2001. He has also been an International Advisor for the International Division of the Association for Educational Communications and Technology. He has published 206 papers and 65 books.